2012
DOI: 10.9753/icce.v33.currents.44
|View full text |Cite
|
Sign up to set email alerts
|

Loading of Vertical Walls by Overtopping Bores Using Pressure and Force Sensors - A Large Scale Model Study

Abstract: This study is based on the data obtained from tests carried out in the Large Wave Flume (Grosser Wellenkanal (GWK)) in Hannover in the frame of a joint research project of Ghent University (Belgium) and Forschungszentrum Küste (FZK, Germany). The goal of the research project is to determine the wave induced loads on vertical storm walls located at the end of overtopped dike, which are designed to protect coastal cities from overtopping and floods. The loads resulting from waves overtopping the dike and impacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Therefore, it is important for designers and owners to recognize the key hazards (e.g., building damage) from the overtopping flow. Chen et al (2012 and Ramachandran et al (2012) reported their laboratory work of overtopping flow loads on vertical structures on a dike crest by physical models at different scales. Common findings of these works suggested that the observed force evolution shape of overtopping flow has a double-peak, which is similar to the "church-roof" time history of wave breaking impact force proposed by Oumeraci et al (1993) for deeper water wave impacts on caissons and composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important for designers and owners to recognize the key hazards (e.g., building damage) from the overtopping flow. Chen et al (2012 and Ramachandran et al (2012) reported their laboratory work of overtopping flow loads on vertical structures on a dike crest by physical models at different scales. Common findings of these works suggested that the observed force evolution shape of overtopping flow has a double-peak, which is similar to the "church-roof" time history of wave breaking impact force proposed by Oumeraci et al (1993) for deeper water wave impacts on caissons and composite structures.…”
Section: Introductionmentioning
confidence: 99%